ANALISIS PENGETAHUAN ORANG TUA TENTANG PENDIDIKAN ANAK USIA DINI DI DESA PULAU SARAK KECAMATAN KAMPAR KABUPATEN KAMPAR - Saprianti Saprianti; Zulirfan Zulirfan; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aimed to analyze the knowledge of parents about early childhood education in Education In The Sarak Island Village Of District Kampar Regency Of Kampar. Conducted in April 2016 to July 2016. This research Samples numbered 46 parents with Random Sampling technique. This type of research used in this research is descriptive. To view the knowledge of parents about early childhood education in the village Sarak Island Kampar District Kampar, then the data collection techniques used were good category test techniques with sufficient and less. Because this study is descriptive, the technique used is quantitative descriptive with percentage. The results of this study are Knowledge Parents About early childhood education at Island Village Sarak Kampar District Kampar regency relatively less seen from several indicators, means of parental knowledge about the understanding of early childhood education, early childhood Objectives, Principles and Benefits of ECD ECD relatively less.Keywords: Early Childhood Education, Knowledge Parents